Manuka Honey and Zein Coatings Impart Bioactive Glass Bone Tissue Scaffolds Antibacterial Properties and Superior Mechanical Properties - Arango-Ospina, Marcela; Lasch, Kristina; Weidinger, Julius; Boccaccini, Aldo R. (Frontiers in Materials, 2021)
The combination of traditional herbal medicine (phytotherapeutic agents) with bioactive glasses is a promising strategy to generate advanced scaffolds for bone tissue engineering (BTE). An old remedy used for wound care since ancient times is honey. The antioxidant, antimicrobial and antibacterial properties of Manuka honey, in particular, make it an attractive substance for application in BTE scaffolds to prevent infections and biofilm formation. In this study 45S5 bioactive glass-based scaffolds produced via the foam replica technique were coated with corn protein zein and Manuka honey with two purposes: to improve the mechanical properties of the brittle scaffolds and to impart antibacterial properties. The morphology and chemical composition of the coated scaffolds were characterized with scanning electron microscopy and Fourier transform infrared spectroscopy, respectively, demonstrating the presence of Manuka honey in the coating. The release of the honey was quantified via ultraviolet-visible spectrophotometry; moreover, the antibacterial activity against Staphylococcus aureus was evaluated via colony-forming units counting and turbidity measurements. Our findings suggest the effective combination of Manuka honey and bioactive glass, adding one more system to the novel family of bioactive glass scaffolds functionalized with phytotherapeutic agents.